Antisite disorder in the battery material - Werner, Johannes; Neef, Christoph; Koo, Changhyun; Zvyagin, S.; Ponomaryov, A.; Klingeler, Rüdiger (Physical review materials, 2020)
We report detailed magnetometry and high-frequency electron spin resonance (HF-ESR) measurements which allow detailed investigation on Li-Fe antisite disorder in single-crystalline LiFePO4, i.e., exchange of Fe2+ and Li+ ions. The data imply that magnetic moments of Fe2+ ions at Li positions do not participate in long-range antiferromagnetic order in LiFePO4 but form quasifree moments. Anisotropy axes of the magnetic moments at antisite defects are attached to the main crystallographic directions. The local character of these moments is confirmed by associated linear resonance branches detected by HF-ESR studies. Magnetic anisotropy shows up in significant zero-field splittings of Δ=220(3) GHz, Δ′∼50 GHz, and a highly anisotropic g factor, i.e., ga=1.4, gb=2.0, and gc=6.3. We demonstrate a general method to precisely determine Fe-antisite disorder in LiFePO4 from magnetic studies which implies a density of paramagnetic Fe2+ ions at Li positions of 0.53%.